William Ogilvie, the Klondike Borderlands and the Making of the Canadian West. Issue 3 (2nd July 2016) - Petrakos, Christopher
ABSTRACT: This article focuses on William Ogilvie, the Canadian Dominions Surveyor and Commissioner of the Yukon during one of the most formative periods in Canadian history—the opening of the Yukon Territories during the Klondike Gold Rush. By the mid-1890s, Canadian and American miners flooded the Yukon–Alaska border in search of gold. The mass migration of American miners created anxieties among Canadian officials who believed Americans would forcibly annex the Yukon Territories. In light of this, Ogilvie was tasked with clarifying the contested boundary line and establishing economic links across the Atlantic to Great Britain in order to secure the Canadian boundary and maintain Canadian authority on the frontier. In 1898, Ogilvie left for Great Britain to tie Canada more closely to the British Empire and, effectively, sell the Yukon to potential British investors. This article thus speaks to issues in the North American borderlands and Atlantic history.